The mediating role of accelerated biological aging in the association between household air pollution from solid cooking fuels and neuropsychiatric disorders - Rui Tang; Haisheng Wu; Ling Jiang; Jie Zhou; Xia Gao; Jiazhen Zheng; Ya-Ping Tang; Mingxi Tang (Ecotoxicology and Environmental Safety)
Background: The role of biological aging in the relationship between household air pollution (HAP) from polluting cooking fuels and neuropsychiatric diseases remains unclear. Methods: This nationwide cohort study enrolled 8550 participants aged 45–80 from 2011 to 2020. Biological age based on Klemera−Doubal method (KDM-BA) was derived from 11 clinical biomarkers. The associations of switching cooking fuels with KDM-BA acceleration (KDM-BAA) and neuropsychiatric diseases were elucidated by generalized linear models and Cox proportional hazard models, respectively. The mediating effects of KDM-BAA on associations between polluting cooking fuel and neuropsychiatric diseases were further examined. We also evaluated the potential of leisure engagement in attenuating KDM-BAA associated with polluting cooking fuels. Results: Compared to consistent use of cleaner fuels, consistent solid fuel use was associated with a 0.12 (95 % CI: 0.05, 0.18) year increase in KDM-BAA, a 25 % higher risk of neurological disease (HR = 1.25, 95 % CI: 1.03, 1.54), and a 34 % increased risk of psychiatric disorders (HR = 1.34, 95 % CI: 1.02, 1.78). Mediation analysis revealed that KDM-BAA significantly mediated the association between solid cooking fuel and neuropsychiatric diseases, with mediated proportions of 5.96 % (P = 0.006) for neurological disease and 5.71 % (P = 0.024) for psychiatric disease. Leisure engagement demonstrated stable benefits in attenuating KDM-BAA independently of cooking fuel use. Conclusion: Our findings illuminate the pathways connecting HAP from solid fuel consumption with biological aging and neuropsychiatric disorders, and highlight the role of leisure engagement and expanding access to cleaner fuels in mitigating these adverse effects.